Perception of Crime Prevention via Environmental Design in Kota Bharu, Kelantan - Akhir, Nor Farah Azira Mohamed (Universiti Sains Malaysia, 2015)
In Kelantan, Malaysia, there is a lack of information about the public’s perception on current crime prevention strategies. Public perception regarding crime prevention through environmental design is important as it emphasizes the proper design and effective use of a created environment to reduce crime. It is a focus of this current study to determine whether the current environmental design is linked to experiences and perception of crime occurrences. Findings in this current study may be salient for the need to improve Kota Bharu’s environment. Therefore, a survey on Kelantanese perception on CPTED elements was conducted. It was calculated that 271 respondents were required for this research. The data analysis methods used were descriptive statistics, One-way ANOVA, Kruskal-Wallis, multi regression and Spearman’s rankorder correlation. The results indicated that there is an association between educational level and crime prevention. Interestingly, there is an association between perceptions of feeling safe and anxiety towards crime, and relationship between crime anxiety and attitudes towards crime prevention. The implications of this study include the need of a well-designed plan of remedial education, extensive campaign on the awareness of crime prevention and sharing safety skills.